2017
DOI: 10.5267/j.ijiec.2016.7.001
|View full text |Cite
|
Sign up to set email alerts
|

Strategic production modeling for defective items with imperfect inspection process, rework, and sales return under two-level trade credit

Abstract: Quality decisions are one of the major decisions in inventory management. It affects customer's demand, loyalty and customer satisfaction and also inventory costs. Every manufacturing process is inherent to have some chance causes of variation which may lead to some defectives in the lot. So, in order to cater the customers with faultless products, an inspection process is inevitable, which may also be prone to errors. Thus for an operations manager, maintaining the quality of the lot and the screening process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…This has been realized by many researchers, as they have collaborated imperfect quality, the screening process, and one/two-stage trade credit policies in their work. Some of the important contributions in this field are those of Zhou et al [40], Khanra et al [41], Khanna et al [42], Palanivel and Uthayakumar [43], Taleizadeh et al [44], and Khanna et al [45]. None of the previous studies that worked on trade credit along with imperfect quality, imperfect inspection, and shortages had presumed the dual bifurcation of customers, i.e., firstly into old and new types (on the basis of past records), and secondly, the new ones into good and bad types (on the basis of partial payment fulfillment) at the whole seller's end, in a three-echelon supply chain.…”
Section: Literature Overviewmentioning
confidence: 99%
“…This has been realized by many researchers, as they have collaborated imperfect quality, the screening process, and one/two-stage trade credit policies in their work. Some of the important contributions in this field are those of Zhou et al [40], Khanra et al [41], Khanna et al [42], Palanivel and Uthayakumar [43], Taleizadeh et al [44], and Khanna et al [45]. None of the previous studies that worked on trade credit along with imperfect quality, imperfect inspection, and shortages had presumed the dual bifurcation of customers, i.e., firstly into old and new types (on the basis of past records), and secondly, the new ones into good and bad types (on the basis of partial payment fulfillment) at the whole seller's end, in a three-echelon supply chain.…”
Section: Literature Overviewmentioning
confidence: 99%
“…Other research focused on diverse imperfect features of manufacturing systems can also be found (e.g. Makis, 1998;Eroglu & Ozdemir, 2007;Chakraborty et al, 2013;Kaylani et al, 2016;Majumder et al, 2016;Zhang et al, 2016;Khanna et al, 2017;Rezazadeh & Khiali-Miab, 2017;Shakoor et al, 2017;Al-Bahkali & Abbas, 2018;Pearce et al, 2018). Because few studies focuse on multiproduct fabrication system by considering an expedited rate and scraps, this research aims to fill the gap.…”
Section: Introductionmentioning
confidence: 99%
“…Solution and performance of these algorithms (including CPU time) were confirmed and assessed via two-sample t-tests to demonstrate their accuracy and efficiency. Diverse aspects of fabrication systems by considering defective items and/or their quality improvement issues were also explored elsewhere (Abilash & Sivapragash, 2016;Balaji et al, 2016;Chiu et al, 2016;Jawla & Singh, 2016;Mičieta et al, 2016;Buckova et al, 2017;Chiu et al, 2017a,b;Khanna et al, 2017).…”
Section: Introductionmentioning
confidence: 99%